Khataman Alquran di Pesantren Sunan Pandanaran Yogyakarta: Kajian Living Hadis - Ainun Hakiemah; Jazilus Sakhok (Jurusan Tafsir Hadis Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2019)
The tradition of khatm al-Qur’an (reading throughout the Qur’an) has been a religious cultural performance which existed since the beginning of pesantren tahfiz Sunan Pandanaran Yogyakarta. The term “khataman” in such pesantren is a term aimed at signifying the annual activities of the completion of some students in memorizing juz ‘amma, certain chosen surah from the Qur’an, and to those students who have completed memorizing the whole Qur’an. This paper aims at tracing the Prophet’s traditions related to the tradition of khatm al-Qur’an and analyzing the sanad and matn of the hadith. I argue that the hadith where the tradition relied upon it was in a degree of marfu‘, the chain of hadith was connected up to the prophet, though, there is a narrator which is classified as majhul al-hal. Nevertheless, the tradition of khatm al-Qur’an has been internalized by the majority of pesantren, including Pesantren Sunan Pandanaran Yogyakarta, where most of santris perceived it as a sacred inauguration and legitimation of their proficient of the Qur’an.